Aid and Foreign Direct Investment: International Evidence - Ugur Karakaplan; Bilin Neyapti; Selin Sayek (Turkish Economic Association, 2005)
Although the literature on the effects of both aid and foreign direct investment (FDI) on development is vast, the relationship between aid and FDI has not been sufficiently explored. This paper empirically investigates the effect of aid on foreign direct investment in view of the hypothesis that countries that receive aid also become more likely to receive FDI. We further claim, however, that this happens especially in cases of good governance and financial market development, and not necessarily otherwise. To test these hypotheses we employ a panel analysis and control for the factors besides aid that are likely to encourage or discourage the FDI flows, such as stability indicators, openness and the income level. The preliminary findings appear to provide robust empirical support for our hypothesis.
Keywords: F35; F41; 330; Foreign aid; FDI